Collision-Free Autonomous Navigation Solution for Mobile Wheeled - Elsergany, Ahmed Moataz Mahmoud (2023)
A Master of Science thesis in Mechanical Engineering by Ahmed Moataz Mahmoud Elsergany entitled, “Collision-Free Autonomous Navigation Solution for Mobile Wheeled”, submitted in April 2023. Thesis advisor is Dr. Mamoun Abdel-Hafez and thesis co-advisor is Dr. Mohammad Jaradat. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).